2016
DOI: 10.1080/10942912.2015.1099044
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Metabolite Analysis of Pickled Wax Gourd in Eastern China by 1H-NMR Spectroscopy and Multivariate Data

Abstract: Pickled wax gourd is a traditional fermented vegetable product popular in Zhejiang province, eastern China; however, information on their quality is quite limited. In the present study, we investigated the quality of pickled wax gourd at different processing phases using nuclear magnetic resonance, principal component analysis, and orthogonal partial least squares-discriminant analysis. According to the spectra of 1 H NMR, 36 kinds of metabolites were found at the 20th day of fermentation. Principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Although ketoglutaric acid has previously been found in pickled wax gourd (Wu et al, 2016), its concentration was low in the samples of this study. Although butyric acid may be associated with the spoilage of fermented cucumbers (Medina et al, 2016), and was not found in the samples from any of the containers on the 6th day, it was evident in low concentrations in all containers on the 12th day.…”
Section: Discussioncontrasting
confidence: 73%
“…Although ketoglutaric acid has previously been found in pickled wax gourd (Wu et al, 2016), its concentration was low in the samples of this study. Although butyric acid may be associated with the spoilage of fermented cucumbers (Medina et al, 2016), and was not found in the samples from any of the containers on the 6th day, it was evident in low concentrations in all containers on the 12th day.…”
Section: Discussioncontrasting
confidence: 73%
“…The conventional analytical instruments for the detection are mass spectrophotometer (MS) or nuclear magnetic resonance (NMR). NMR metabolomics has been successfully applied in analyzing complex sample matrices in food chemistry, toxicology and environmental studies [ 19 , 20 ]. It is also being used in the medicinal and pharmacological fields in detecting putative biomarkers, especially biomarkers related to the pathogenesis of the disease and testing for a new lead compound [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…NMR metabolomics has been successfully applied in analyzing complex sample matrices in food chemistry, toxicology and environmental studies [ 19 , 20 ]. It is also being used in the medicinal and pharmacological fields in detecting putative biomarkers, especially biomarkers related to the pathogenesis of the disease and testing for a new lead compound [ 19 ]. The information generated from these data can help clinicians and researchers understand the efficacy of the treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] In recent years, it has been widely used in several fields, such as agriculture, food chemistry, toxicology, and medicine. [22,23] A lot of high throughput metabolomics methodologies are currently available, and among them, proton nuclear magnetic resonance ( 1 H NMR) is more preferred due its robustness, reproducibility, and nondestructiveness. [20,24] The 1 H-NMR is an emerging leading analytical tool in metabolomics studies due to a large number of identified compounds.…”
Section: Introductionmentioning
confidence: 99%